Distorted Prices and Targeted Taxes in the New Keynesian Network Model - Anastasiia Antonova; Gernot Müller (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
When confronted with sectoral shocks, policymakers often resort to targeted, sector-specific taxes in an ad hoc fashion. Based on the New Keynesian Network model, we characterize the optimal tax response to sectoral shocks: it features twice as many tax instruments as there are sectors, is budget-neutral, and not confined to the sector where the shock originates. We show that the optimal policy can be approximated by a simple rule that responds to inflation in the shocked sector and adjusts tax instruments in other sectors according to input-output linkages. We study its quantitative performance in a calibrated version of the model.
Keywords: E32; E62; 330; sectoral shocks; sales taxes; production subsides